BASIC ISSUES IN SPEECH PERCEPTION - Rafika Nurhidayah (Jurnal Ilmiah Spectral, 2019)
Speech is the primary means by which humans communicate with each other. When we listen to someone speaking we generally focus on understanding their meaning. We are trying to interpret what does the speaker want to tell us by generating the ideas of the language she/he produces. Since the language is series of sound that has meaning, the perception of speech involves the recognition of patterns in the acoustic signal in both time and frequency. It is much easier to get the meaning of a conversation if both the speaker and the listener has same language. But, if both of them has different language it will take time to get the clear meaning of a conversation. This paper is trying to examine the basic issues in speech perception that human beings face everyday consciously or unconsciously.